Distinct Neutrophil Populations in the Spleen During PICS - Sengupta, Satarupa; Caldwell, Charles C.; Nomellini, Vanessa (Frontiers in Immunology, 2020)
While mortality after acute sepsis has decreased, the long-term recovery for survivors is still poor, particularly those developing Persistent inflammation, Immunosuppression, and Catabolism Syndrome (PICS). While previously thought that activated neutrophils responding to the acute phase of sepsis migrate to the spleen to undergo cell death and contribute to immunosuppression, our data show a significant accumulation of distinct, yet functional, neutrophil populations in the spleen in a murine model of PICS. The exact role and function of neutrophils in this response is still unclear. The objective of our study was to better define the immune function of splenic neutrophils to determine if this could give insight into the pathogenesis of PICS. Using a murine model of cecal ligation and puncture (CLP), which demonstrates all characteristics of PICS by eight days, spleens were harvested, and neutrophils were identified by Ly6G and CD11b expression via flow cytometry. Nearly all splenic neutrophils expressed CD54, but there were distinct CD54hi and CD54lo cells, with the majority being CD54lo cells during PICS. The CD54hi population showed traditional, pro-inflammatory properties, but a relatively decreased chemotactic response, while CD54lo cells had significantly higher chemotaxis, yet significantly decreased pro-inflammatory functions. Using EdU incorporation, we found that the CD54hi population on day two after CLP may be participating in emergency myelopoiesis. However, the vast majority of the CD54lo population were paused in the G1 phase at this time point and not proliferating. By day eight after CLP, most of the CD54hi cells in the spleen were no longer proliferating, while the CD54lo cells were, indicating that CD54lo dominate in extra-medullary myelopoiesis at later time points. Almost none of the neutrophils produced arginase or iNOS, indicating these are not suppressor cells. Overall, our data demonstrate that neutrophil accumulation in the spleen during PICS is related to extra-medullary myelopoiesis, leading to the production of immature neutrophils. While not suppressor cells, the majority have greater chemotactic function, but less inflammatory responsiveness, which may contribute to the immunosuppression seen in PICS. Attention to these distinct neutrophil populations after septic or other systemic inflammatory responses is therefore critical to understanding the mechanisms of PICS.